PEMANFAATAN LIMBAH CAIRAN PULPA HASIL SAMPING FERMENTASI BIJI KAKAO SEBAGAI BAHAN DASAR ASAM ASETAT DENGAN PROSES DISTILASI - Mirah Mahadewi, Anak Agung Sagung; Ganda Putra, G.Putu; Wrasiati, Ni Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2014)
This study aims (1) to determine the effect of ratio between material and water solvent, and distillation time on the characteristics of acetic acid produced from the pulp liquid waste by product of fermented cocoa beans, and (2) to determine the ratio between material and water solvent, and distillation time which produces the most potential distillate that can be used as a basic ingredient to produce the best acetic acid. The experiments in this study were using a randomized block factorial design (RBFD) with 2 factors. The first factor was the ratio of material and water solvent (A) which consists of three levels, i.e. 1:1, 1:2, 1:3, and the second factor was the distillation time (B) which consists of three levels, i.e. 10, 20, 30 minutes. Research was carried out 2 times, therefore it was found 9 treatment combinations that were grouped into 18 experimental units. The treatment of ratio between material and water solvent affects the percentage yield of distillate, pH, total acid and acetic acid. The treatment of distillation time affects the percentage yield of distillate, pH, total acid and acetic acid. The interaction treatment A and B significantly affects the percentage yield of distillate, but it does not affect pH, total acid and acetic acid. The ratio between material and water solvent (1:1) with distillation time of 30 minutes is able to produce the most potential distillate that can be used as a basic ingredient to produce the highest percentage of distillate yield of 69.50%, pH 2.95, total acid 0.04 meq NaOH/g, and 0.22% acetic acid.
Keywords: 19